2021
DOI: 10.1039/d1ra03629g
|View full text |Cite
|
Sign up to set email alerts
|

Development of pyrazoline-based derivatives as aminopeptidase N inhibitors to overcome cancer invasion and metastasis

Abstract: Compound 2k exhibited promising in vitro anti-invasion and in vivo anti-metastasis potencies, suggesting its prospect as an anti-invasion and anti-metastasis lead.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The results are listed in Table 1 . Similar to SARs previously reported, the substituents on the terminal phenyl group of the diphenyl pyrazoline moiety could significantly impact the inhibitory activities against APN [ 30 ]. Comparing mono-substituted compounds 14a – 14f with a methyl group as R 1 , it was easily found that compounds ( 14a , 14d ) with ortho -substituents showed better inhibitory potencies against APN than their counterparts with meta -substituents ( 14b , 14e ) or para -substituents ( 14c , 14f ), respectively.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…The results are listed in Table 1 . Similar to SARs previously reported, the substituents on the terminal phenyl group of the diphenyl pyrazoline moiety could significantly impact the inhibitory activities against APN [ 30 ]. Comparing mono-substituted compounds 14a – 14f with a methyl group as R 1 , it was easily found that compounds ( 14a , 14d ) with ortho -substituents showed better inhibitory potencies against APN than their counterparts with meta -substituents ( 14b , 14e ) or para -substituents ( 14c , 14f ), respectively.…”
Section: Resultssupporting
confidence: 69%
“…Compounds 18a – 18h , 18j , 18k , 18m and 18n were reported before [ 30 ]. Compounds 18i , 18l , 18o , 18p and 18r – 18w were prepared following the procedure described for the compound 18q .…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Such heterocyclic scaffolds having the nitrogen and/or sulfur atoms are involved in coordination of the zinc ion, and their rigidness is usually favored for formation of the desired hydrophobic interactions. 8,9…”
Section: Introductionmentioning
confidence: 99%
“…Proliferating active tumor cells may be inhibited by low expression of aminopeptidase. This provides the rationale that aminopeptidase can be used as a new therapeutic approach [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%